2004
DOI: 10.1096/fj.04-2445com
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐2 null mice exhibit an early onset and severe experimental autoimmune encephalomyelitis due to an increase in MMP‐9 expression and activity

Abstract: Matrix metalloproteinase-2 (MMP-2; gelatinase A) is known to degrade a broad range of extracellular matrix components and chemokines, and has important roles in the processes of cell migration, invasion, and involution during development, as well as during tumor growth and metastasis and in inflammation and repair. To better elucidate the roles of this matrix metalloproteinase in the development and progression of experimental autoimmune encephalomyelitis, we used MMP-2-deficient (KO) mice. Surprisingly, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 40 publications
5
76
3
Order By: Relevance
“…Purified Hsp70 has been shown to act as a novel cytokine, which causes monocytes to express proinflammatory cytokines such as IL-1, IL-6, and TNF- (Asea et al, 2000;Esparza et al, 2004). However, other reports suggested that Hsp70-mediated induction of proinflammatory cytokines might be due to contamination by LPS as well as LPS-associated molecules (Gao and Tsan, 2003a, b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified Hsp70 has been shown to act as a novel cytokine, which causes monocytes to express proinflammatory cytokines such as IL-1, IL-6, and TNF- (Asea et al, 2000;Esparza et al, 2004). However, other reports suggested that Hsp70-mediated induction of proinflammatory cytokines might be due to contamination by LPS as well as LPS-associated molecules (Gao and Tsan, 2003a, b).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of reports on the secretion of Hsp70 independent of necrotic cell death (Hightower et al, 1989;Broquet et al, 2003;Esparza et al, 2004;Hunter-Lavis et al, 2004;Adewoye et al, 2005;Dybdahl et al, 2005;Svensson et al, 2005). To explore whether Hsp70 could be released from Hsp70 transfectants to the culture medium, Hsp70 and mock transfectants were cultured in the absence or presence of PMA, and the amount of Hsp70 released in the culture medium was then measured by Western blot analysis.…”
Section: Hsp70 Is Secreted From the Cells To Culture Supernatants Anmentioning
confidence: 99%
“…Current data indicate that MMP12 contributes to emphysema 113,114 , whereas MMP3 and MMP9 contribute to skin inflammatory conditions 89,115 . By contrast, MMP8 protects against skin inflammatory responses 104 and MMP2 protects against inflammation of the brain and spinal cord 116 . Collectively, these observations indicate that MMPs function non-redundantly to regulate inflammation, which is potentially of great medical significance.…”
Section: Mmps In Human Inflammatory Disease Modelsmentioning
confidence: 98%
“…In this study, we show anomalous MMP-9 upregulation in the spinal cord-injured MMP-2 null animal. Similarly, MMP-9 is upregulated in a model of experimental autoimmune encephalomyelitis in MMP-2 null mice (Esparza et al, 2004). As a consequence of compensatory MMP-9 upregulation in lymphocytes and endothelial cells, MMP-2 null mice display an early onset of the disease with a worsened outcome.…”
Section: Glial Scar Formation and Mmp-2mentioning
confidence: 99%